PROTOTYPE AIR CONDITIONING MONITORING AND CONTROL SYSTEM FOR SMART CLASSROOM BASED ON THE INTERNET OF THINGS - samuel beta; rindang reynaldi; gisnaya faridatul avisyah (Politeknik Negeri Semarang, 2023)
Electricity wastage is a growing concern, often resulting from human behavior. One common scenario is the continuous operation of a high-powered air conditioner (AC) even when it's unnecessary. Moreover, extended AC usage can accelerate wear and tear, potentially damaging the unit. To address these issues, a remote monitoring and control device based on the Internet of Things (IoT) concept is crucial. This device can connect to smartphones, allowing users to remotely monitor and control AC usage. Through an AC simulator, the system enables monitoring and control via a telegram system linked to the smartphone. Developed using the waterfall method and utilizing the NodeMCU ESP8266 microcontroller, the prototype proves effective in assisting users in monitoring and controlling AC usage. Particularly useful when users are away from the AC location and inadvertently forget to turn it off, the system mitigates unnecessary electricity wastage. By implementing this solution, energy efficiency is promoted, and the lifespan of AC units is extended. With the potential to reduce electricity wastage, this technology contributes to a more sustainable future.